Психологічні особливості гармонійного шлюбу : магістерський дослідницький проект - Константінова, Алла Георгіївна (Одеса : НУ "ОЮА", 2024)
Шляхом теоретико-методологічного аналізу наукових досліджень встановлено, що гармонія шлюбних стосунків передбачає взаємну згоду, внутрішню і зовнішню взаємну злагодженість подружжя. За допомогою кількісного аналізу виявлено провідні елементи сімейної ідеології, які формують соціальний клімат сім'ї. Встановлено, що серед «Показників відносин» між членами сім'ї найбільший пріорітет надається показникам Згуртованості, Експресивності. За «Показниками особистісного зростання» найбільше значення має Орієнтація на активний відпочинок, Інтелектуально-культурна орієнтація та Орієнтація на досягнення. Менше уваги приділяється Незалежності. Серед «Показників управління сімейною системою», найбільш цінним для більшості виявився показник Організація і Контроль. Встановлено достатню гармонійність шлюбно-сімейних стосунків та переважання у вибірці гедоністичних та зближаючих почуттів. Кількісний аналіз Напруженості міжособистісних відносин засвідчив стриманість у вираженні агресивних та віддаляючих почуттів. «Індекс дисгармонійності відносин» встановив, що 24,3% досліджуваних мають високі значення дисгармонії в міжособистісних відносинах: відсутня єдність, згода, ослаблені позитивні емоційні зв'язки. 30,5% респондентів мають достатню гармонію у відносинах, відкритість, стабільність, що передбачає тривале збереження взаємодії в парі. У 45,7% опитаних надмірно виражені почуття, що зближують. Здійснено добір психологічних рекомендацій і тренінгових вправ для гармонізації стосунків. Through the theoretical and methodological analysis of scientific research, it was established that the harmony of marital relations implies mutual consent, internal and external mutual harmony of spouses. A program of empirical research into the psychological features of a harmonious marriage has been developed. With the help of quantitative analysis, the leading elements of family ideology, which shape the social climate of the family, were revealed. It was established that among the "Indicators of relations" between family members, the highest priority is given to the indicators of Cohesion and Expressiveness. According to "Indicators of personal growth". Orientation to active recreation, Intellectual and cultural orientation and Orientation to achievement are of the greatest importance. Less attention is paid to independence and moral and ethical aspects of interaction. Among the "Family System Management Indicators", the Organization and Control indicator was the most valuable for the majority. Sufficient harmony of marital and family relations and predominance of hedonistic and converging feelings in the sample were established. Quantitative analysis of the tension of interpersonal relations proved restraint in the expression of aggressive and distant feelings.The "Relationship Disharmony Index" found that 24.3% of the respondents have high levels of disharmony in interpersonal relationships: lack of unity, agreement with other people, weakened positive emotional ties. 30.5% of respondents have average values, which indicates sufficient harmony in relations, openness, stability, which implies long-term preservation of interaction in a couple. 45.7% of respondents have low values of relationship disharmony - possible, excessively expressed feelings that bring people together, such as unity, commonality between people, companionship, kindness, gratitude, respect, love. A selection of psychological recommendations and training exercises for the harmonization of marital relations was made
Константінова А. Г. Психологічні особливості гармонійного шлюбу : магістерський дослідницький проект / А. Г. Константінова. - Одеса : НУ "ОЮА", 2024. - 63 с.
Keywords: psychological features; harmonious marriage; disharmony; family relations; marital relations; психологічні особливості; гармонійний шлюб; дисгармонія; сімейні стосунки; шлюбні відносини